Ecological Analysis of Five Years Dengue Cases and Outbreaks in Keningau, Sabah, Malaysia - Mohd Shafik Abd Majid; Mohd Rohaizat Hassan; Wan Rosmawati Wan Ismail; Abdul Marsudi Manah; Syed Sharizman Syed Abdul Rahim; Mohammad Saffree Jeffree (Malaysian Journal of Medicine and Health Sciences, 2020)
Introduction: Dengue fever is caused by the dengue virus that is transmitted via Aedes mosquitoes. The lifecycle of Aedes mosquitoes is affected by the local climate (rainfall) which influences dengue transmission. Sabah is one of the states that is laden with a high incidence rate of dengue in Malaysia and the condition seems to have worsened with sudden, multiple outbreaks occurring in the year 2016. Methods: An ecological analysis was conducted in Keningau, Sabah to analyse dengue case patterns and distribution over a 5-year period and to exhibit the correlation between rainfall, larval indices, dengue incidences, and outbreaks. Results: Significant cross-correlation analysis (CCF) was discovered between rainfall and Aedes index at lag number 5 with a correlation coefficient of 0.151 (±0.063) as well as between rainfall and Breteau Index at lag number 5 with a correlation coefficient of 0.143 (±0.063). However, no significant cross-correlation analysis was found between Aedes index and dengue incidences. Associations were also seen between larval indices and outbreak cases. Conclusion: This study showed an increase of Aedes and Breteau Indices to susceptibility level five weeks after rainfall which increases the risk of dengue transmission.